Axillary reverse mapping in N0 patients requiring sentinel lymph node biopsy – A systematic review of the literature and necessity of a randomised study. (June 2017) - Parks, R.M.; Cheung, K.L.
Abstract: Objectives: Axillary reverse mapping (ARM) is a technique to map and preserve arm lymphatics which may be damaged during surgery, resulting in lymphoedema. This work systematically reviews the incidence of lymphoedema following sentinel lymph node biopsy (SLNB) + ARM, compared to SLNB alone, for clinically node negative disease, as well as recurrence rate, other morbidity and the feasibility and difficulties of ARM. Materials and Methods: The following databases were searched: PubMed, Embase, Cochrane Library. Abstracts submitted to recognised societies dedicated to research in oncology were included. Studies were eligible if performed within the last 10 years; ARM was used in any form; ARM performed during SLNB ± axillary lymph node dissection (ALND). Studies were analysed using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results: No studies were found meeting the initial inclusion criteria. Therefore, studies reporting use of SLNB + ARM (i.e. no comparison to SLNB) were reviewed. A second search was performed to identify studies reporting outcome following SLNB alone. Twelve studies reported data on patients undergoing SLNB + ARM and 23 studies on patients undergoing SLNB. Incidence of lymphoedema following SLNB + ARM was quoted between 0-4% and 0–63.4% following SLNB. Few studies commented on recurrence rate. Studies included were of mainly low level of evidence. Conclusion: Evidence is beginning to emerge for the use of ARM in order to reduce lymphoedema following axillary surgery. However, data regarding oncological safety of ARM is not clear and randomised controlled trials, with adequate follow-up, need to be performed to determine this. Highlights: Incidence of lymphoedema following SLNB for N0 disease is already low. ARM in addition to this may safely reduce lymphoedema further. A randomised controlled trial is necessary, however, difficult to implement.